3D discrete element simulation of a geotextile-encased stone column under uniaxial compression testing. (October 2020) - Tan, Xin; Hu, Zhengbo; Cao, Ming; Chen, Changfu
Abstract: The geotextile encased stone column has been numerically modeled with the DEM gravel specimen wrapped by the finite-element shell structure. The irregular shape and size distribution of gravels have been simulated according to the experimental data using the rigid block module in PFC. The geotextile encasement has been modeled using the geogrid elements in FLAC3D. The complete stress–strain behaviors of the geotextile encased stone column under the uniaxial compression are successfully predicted and show good agreement with experiments. The failure of the encased stone column is controlled by the geotextile encasement, which might be raptured due to the column expansion and stabbing from irregularly shaped gravels. Without considering the stress concentration effect, the continuum-based models overestimate the bearing capacity of the geotextile encased stone column.